2018
DOI: 10.1007/s12602-018-9399-6
|View full text |Cite
|
Sign up to set email alerts
|

Septicemia from Lactobacillus rhamnosus GG, from a Probiotic Enriched Yogurt, in a Patient with Autologous Stem Cell Transplantation

Abstract: Probiotic-rich foods are consumed without much restriction. We report here, a case of septic shock caused by yogurt derived Lactobacillus species in a 54-year-old male patient with acute promyelocytic leukemia, in second complete remission, and who was an autologous stem cell transplantation recipient. He received high dose chemotherapy and autologous peripheral blood stem cell transplantation. He ingested commercially available probiotic-enriched yogurt because of severe diarrhea. One week later, he developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
0
29
0
3
Order By: Relevance
“…The pathogen was identified by strain-specific polymerase chain reaction analysis to be identical to the Lactobacillus rhamnosus GG found in the yogurt. 132 …”
Section: Resultsmentioning
confidence: 99%
“…The pathogen was identified by strain-specific polymerase chain reaction analysis to be identical to the Lactobacillus rhamnosus GG found in the yogurt. 132 …”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic administration of Lactobacillus plantarum (probiotics) has proven to be safe and feasible in children and adolescents undergoing allo-HSCT [35], whereas another randomized clinical trial using Lactobacillus rhamnosus GG failed to alter the intestinal microbiome and GVHD incidence [36]. In addition, several case reports have suggested that the probiotic itself caused septicemia in highly immunocompromised HSCT recipients [37][38][39]. Fecal microbiota transplantation may be an alternative treatment option for severe GI-GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…A bacteremia associada ao uso de probióticos, especialmente em pacientes imunossuprimidos, é um risco e, no estudo de Koyama et al 10 , a septicemia causada pela ingestão voluntária de iogurtes disponíveis comercialmente levou ao quadro de choque, assim, não só os benefícios, mas os riscos do uso de probióticos são fatores relevantes a serem considerados quanto à administração de probióticos para pacientes submetidos ao TCTH, fator relevante a ser considerado. De modo geral, os probióticos são considerados seguros, tendo em vista sua ampla utilização na indústria de alimentos.…”
Section: Discussionunclassified